Resilience assessment of the social-ecological system of medium and large landowners of Cotriguaçu (MT, Brazil) - Bernasconi, Paula; Buschbacher, Robert; Schuster, Elison Marcelo; da Silva, Solange Arrolho; Baby, Andre; Gislon, Ledyany; Grabert, Mônica; Schütz, Dariane (Sustainability in Debate, 2016)
The aim of this study is to understand the dynamics of the medium and large rural landowners in Cotriguaçu, Mato Grosso and discuss their resilience as a complex social-ecological system (SES). For that purpose, a historical assessment was conducted; attributes, key variables and drivers, and the panarchy involving systems of other scales were characterized; and future scenarios were developed. The methodology involved participatory assessments, interviews and evaluation by experts. The conclusion and final discussion focus on the resilience assessment for the focal system, and on the applicability of this tool for research and environmental management in the Amazon. Among other aspects, the discussion emphasizes the importance of developing public policy and management with an adaptive approach rather than on static solutions that will inevitably be temporary and subject to changes and future problems.